2000
DOI: 10.1111/j.1471-0528.2000.tb10401.x
|View full text |Cite
|
Sign up to set email alerts
|

Cord blood oxygen saturation in vigorous infants at birth: what is normal?

Abstract: Objective To define the normal ranges of umbilical cord blood oxygen saturation (SaO,) and acid-base status at birth and to evaluate the effect of gestational age on cord blood values in vigorous newborn infants following spontaneous vaginal birth from a vertex position.Design Prospective study.Setting Department of Obstetrics and Gynaecology, University of Graz, Austria.Sample Cord blood samples from 1281 vigorous newborn infants.Methods Cord blood sampling was performed following on newborn infants following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
0
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 23 publications
7
36
0
5
Order By: Relevance
“…This approach that we propose strikes a balance from costly over-investigation of thousands of normal deliveries (with extra burden on staff), while acknowledging the considerable error rate in sampling that we and others 3,4 have now consistently found. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach that we propose strikes a balance from costly over-investigation of thousands of normal deliveries (with extra burden on staff), while acknowledging the considerable error rate in sampling that we and others 3,4 have now consistently found. …”
Section: Discussionmentioning
confidence: 99%
“…We then determined the proportion of invalid samples using criteria described by Westgate et al 3 and adopted by others 4 . Specifically, for samples to be valid, the pH in the vein should be > 0.02 relative to the artery, and CO 2 < À4 mmHg.…”
Section: Methodsmentioning
confidence: 99%
“…Very little attention was given to the oxygen concentration present in culture media. Oxygen concentrations in human body vary from 3 to 11 % (Goossens et al 2011) and the stem cells reside in the most hypoxic areas (Roemeling-van et al 2013;Danet et al 2003), thus, hUCB-MSCs reside in anatomical sites that are relatively oxygen-deficient (Arikan et al 2000). Studies in vitro have shown that culture in 2-3 % O 2 stimulated human mesenchymal stem cells (hMSC) proliferation (Estrada et al 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Dans les autres é tudes ré alisé es concernant la validation des gazomé tries, ce pourcentage varie entre 6 % pour Arikan et al [15], 13 % pour Victory et al [7], 14 % pour Kro et al [11], 18,3 % pour Tong et al [16], et 19,4 % pour Westgate et al [10]. Une diffé rence est cependant à noter concernant notre é tude ; nous avons utilisé des critè res plus restrictifs que Westgate et al [10], Arikan et al [15], Victory et al [7] et Tong et al [16], ce qui pourrait expliquer que nous avons un pourcentage de gazomé tries non fiables un peu plus é levé que la moyenne.…”
Section: Discussionunclassified
“…Premiè rement, nous avons é tabli leur faisabilité , dé finie par le rapport de gazomé tries complè tes sur le nombre d'accouchements d'enfants né s vivants. Deuxiè mement, nous avons é tabli leur fiabilité , dé finie par le rapport des gazomé tries qui remplissaient les critè res de qualité initialement dé finis par Westgate 3] ; p < 0,0001) aboutissaient à des gazomé tries non valides, alors que seulement 11,3 % des cé sariennes prophylactiques (IC 95 % [4,[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]2] ; p < 0,0001) donnaient lieu à des gazomé tries non valides. Faisabilité et fiabilité é taient donc significativement plus faibles lors des cé sariennes en urgence.…”
Section: R é S U M éunclassified